CONSUMER EDUCATION, FAMILY AND REFERENCE GROUP INFLUENCE IN ASO EBI SELECTION IN SOUTHWEST NIGERIA - Olugbamigbe, Abigail Olukemi (Journal of Child, Family, and Consumer Studies, 2024)
In Nigeria, the selection of aso ebi, a traditional attire worn for special occasions, is influenced by various social and familial factors. This study examined the relationship between family influence, reference group influence, and consumer education in the selection of aso ebi in Southwest Nigeria. Two research questions were posed, and two hypotheses were tested at a 0.05 level of significance. A correlational design was employed to collect data from 1200 adult individuals (aged 18 years and above) in the Southwestern geopolitical zone of Nigeria, covering Ekiti, Lagos, Ogun, Ondo, Osun, and Oyo states. A validated, reliable, self-structured questionnaire titled "Consumer Education and Behaviour in the Choice of Aso Ebi Questionnaire (CEBCAQ)" was used for data collection. Data analysis was conducted using Pearson’s r and Fisher's Z statistics. Findings revealed a positive but low correlation between consumer education and both family (r = 0.10) and reference group purchasing behaviour (r = 0.14) in aso ebi selection. The relationship between consumer education and consumer behaviour was significantly stronger among male adults than female adults (rmales = 0.62, rfemales = 0.49, Zcal > Ztab); and significantly stronger among older adults than younger adults (rold =0.59, ryoung = 0.48, Zcal > Ztab). The study concludes that the complex interplay of social pressure, family dynamics, reference groups, and economic factors influencing aso ebi choices aligns with consumer behaviour surrounding clothing articles globally. Future research could explore how consumer education programs may be tailored to target families and address social influences in aso ebi selection.